2017
DOI: 10.1107/s2053229617011366
|View full text |Cite
|
Sign up to set email alerts
|

A bipyridine-ligated zinc(II) complex with bridging flavonolate ligation: synthesis, characterization, and visible-light-induced CO release reactivity

Abstract: Metal-flavonolate compounds are of significant current interest as synthetic models for quercetinase enzymes and as bioactive compounds of importance to human health. Zinc-3-hydroxyflavonolate compounds, including those of quercetin, kampferol, and morin, generally exhibit bidentate coordination to a single Zn center. The bipyridine-ligated zinc-flavonolate compound reported herein, namely bis(μ-4-oxo-2-phenyl-4H-chromen-3-olato)-κO:O,O;κO,O:O-bis[(2,2'-bipyridine-κN,N')zinc(II)] bis(perchlorate), {[Zn(CHO)(CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The photoreactivity of Pb II and Al III flavonolato complexes is suppressed, whereas Zn II complexes exhibit similar reactivity to free 3-hydroxyflavone . The flavonolate complex [(6-R 2 TPA)­Zn­(3-Hfl)]­ClO 4 (TPA = tris­(2-pyridyl­methyl)­amine) 199 (Figure ), Zn II complexes bearing tetradentate tripodal nitrogen donor ligands and flavonol derivatives 200 or 201 , and the bipyridine-ligated Zn II complex 202 with a bridging flavonolate ligand all released CO upon irradiation at λ irr > 400 nm. In addition, the Ru II cymene complex 203 released CO upon irradiation at either 300 or 419 nm .…”
Section: Photorelease Of Gasotransmittersmentioning
confidence: 99%
“…The photoreactivity of Pb II and Al III flavonolato complexes is suppressed, whereas Zn II complexes exhibit similar reactivity to free 3-hydroxyflavone . The flavonolate complex [(6-R 2 TPA)­Zn­(3-Hfl)]­ClO 4 (TPA = tris­(2-pyridyl­methyl)­amine) 199 (Figure ), Zn II complexes bearing tetradentate tripodal nitrogen donor ligands and flavonol derivatives 200 or 201 , and the bipyridine-ligated Zn II complex 202 with a bridging flavonolate ligand all released CO upon irradiation at λ irr > 400 nm. In addition, the Ru II cymene complex 203 released CO upon irradiation at either 300 or 419 nm .…”
Section: Photorelease Of Gasotransmittersmentioning
confidence: 99%
“…The coordination sphere in the complex [Zn(Flav- O , O )(H 2 O)2(SO 3 ) 2 ] [ 294 ] is completed by bidentate Flav- O , O ligand with two waters in equatorial positions and two sulfonyl oxygen atoms (from adjacent complex) in axial positions, which leads to assembling the 1D-ladder-like chain coordination polymer. Complex [Zn(Flav- O , O )(bipy- N , N )(ClO 4 ) 2 ] [ 295 ] is dinuclear bridging via nitrogens and oxygens with weakly bound perchlorate ions. Complex [Zn(Flav- O , O ) 2 (temed- N , N )] [ 296 ] has distorted octahedral geometry with bidentate mode of ligands.…”
Section: Binding Motifs and Supramolecular Architecture For Crystal Structure Of Plant Compounds And Their Metal Complexesmentioning
confidence: 99%
“…Our laboratory has recently demonstrated that divalent metal complexes of the general formula [(L)Zn(3-Hfl)]ClO 4 , containing a coordinated 3-hydroxyflavonolato ligand and supported by a chelating nitrogen donor ligand (L), undergo clean UV- or visible light-induced reactivity in the presence of O 2 to produce one equivalent of CO (determined by GC head space analysis) and a metal carboxylate (depside) complex (Scheme 16) [95,96,97,98,99]. The reaction quantum yield (Table 1) for CO release from these complexes depends on the ligand secondary environment of the metal complex or solvent conditions, and on the divalent metal ion present.…”
Section: Co Production From 3-hydroxyflavones Via Photochemical Rementioning
confidence: 99%
“…The reaction quantum yield (Table 1) for CO release from these complexes depends on the ligand secondary environment of the metal complex or solvent conditions, and on the divalent metal ion present. Divalent zinc 3-hydroxyflavonolato complexes of a variety of supporting chelate ligands exhibit reaction quantum yields for CO release that can be tuned from ~0.0003 to 0.012 [95,98,99]. Encapsulation of the Zn(II)-flavonolato moiety within a hydrophobic microenvironment produced the highest reaction quantum yield whereas positioning the Zn(II) 3-hydroxyflavonolato unit within a hydrogen bond donor pocket produced the least reactive complex.…”
Section: Co Production From 3-hydroxyflavones Via Photochemical Rementioning
confidence: 99%